Vermanšaft na Gorenjskem - Kokalj Kočevar, Monika (Studia Historica Slovenica, 2016)
Based on archive material the author presents the before- and after military formation of the Wehrmannschaft in Gorenjska which was established in accordance with the German model and similar arrangements in occupied territories with civilian administration, with an agreement with the head of civilian administration and a group of armed detachments of the German national socialist party, SA Gruppe Südmark that oversaw south Carinthia in the summer of 1941. Presented here is the formation of the leadership of the Wehrmannschaft in Gorenjska, the formation of units, condition of its manpower, training, activities and integration in other units.
Keywords: civilna obramba; civilna zaščita; druga svetovna vojna; Gorenjska; Koroška; Koroška ljudska zveza; mobilizacija; oboroževanje; Slovenija; svetovna vojna 1939-1945